2008
DOI: 10.1152/ajpheart.00873.2007
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic actions of metformin in the heart can occur by AMPK-independent mechanisms

Abstract: The metabolic actions of the antidiabetic agent metformin reportedly occur via the activation of the AMP-activated protein kinase (AMPK) in the heart and other tissues in the presence or absence of changes in cellular energy status. In this study, we tested the hypothesis that metformin has AMPK-independent effects on metabolism in heart muscle. Fatty acid oxidation and glucose utilization (glycolysis and glucose uptake) were measured in isolated working hearts from halothane-anesthetized male Sprague-Dawley r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
56
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 71 publications
4
56
2
Order By: Relevance
“…However, chronic subcutaneous infusion of 150 mg/kg/24 h metformin did not activate AMPK phosphorylation in heart. In agreement with our study, an AMPK-independent effect of metformin was recently reported, in which the administration of 2 mM metformin did not alter AMPK activity in the heart of Sprague-Dawley rats and H9C2 cells although metformin altered fatty acid oxidation and glucose utilization [40]. Metformin also does not increase AMPK activity in mice liver, while it reduces alcohol-induced hepatic lipid accumulation [41].…”
Section: Discussionsupporting
confidence: 92%
“…However, chronic subcutaneous infusion of 150 mg/kg/24 h metformin did not activate AMPK phosphorylation in heart. In agreement with our study, an AMPK-independent effect of metformin was recently reported, in which the administration of 2 mM metformin did not alter AMPK activity in the heart of Sprague-Dawley rats and H9C2 cells although metformin altered fatty acid oxidation and glucose utilization [40]. Metformin also does not increase AMPK activity in mice liver, while it reduces alcohol-induced hepatic lipid accumulation [41].…”
Section: Discussionsupporting
confidence: 92%
“…These autophagy-independent effects of AMPK may account for the ability of metformin to protect the diabetic heart. It is also possible that metformin can use AMPK-independent mechanisms to confer cardioprotection in diabetes (55).…”
Section: Discussionmentioning
confidence: 99%
“…HER2 suppression, however, can sufficiently be blocked by knockdown of the PP2A and mTOR target p70S6kinase, pointing at a PP2A/mTOR-dependent mechanism underlying metformin function. Also, some of the metabolic effects seen in isolated working rat hearts and cultures of heart-derived cells after metformin treatment clearly seem AMPK independent (32). In accordance with these data, we show here that metformin has an immediate effect on the phosphorylation of the PP2A/mTOR targets p70S6 kinase, S6, and tau, but does not show a significant influence on the phosphorylation of the AMPK target ACC, and only a comparably small effect on AMPK itself in primary cortical neurons at the concentrations used here.…”
Section: Discussionmentioning
confidence: 99%